Aedes japonicus japonicus (Diptera: Culicidae) arrives at the most easterly point in North America. Issue 6 (16th February 2015) - Fielden, Miles A.; Chaulk, Andrew C.; Bassett, Kate; Wiersma, Yolanda F.; Erbland, Mardon; Whitney, Hugh; Chapman, Thomas W.
Abstract: Aedes japonicus japonicus (Theobald) (Diptera: Culicidae), the Asian bush mosquito, is a keen biter linked to the transmission to humans of a variety of diseases. It has moved significantly from its historical Asian distribution, with its arrival in North America first noted in 1998 in New York and New Jersey, United States of America. Here we report the presence of A . j . japonicus within our collections of mosquitoes in the capital city of the easternmost province in Canada: St. John's, Newfoundland and Labrador, in 2013. This observation provides further evidence of this mosquito's ability to significantly expand its geographic range, potentially affecting connectivity between subpopulations globally. Résumé: Aedes japonicus japonicus (Theobald) (Diptera: Culicidae), le moustique asiatique Bush, transmet aux humains une variété de maladies via ses piqûres. L'espèce a augmenté son aire de distribution de façon significative, à partir d'une répartition historique en Asie jusqu'à son arrivée en Amérique du Nord en 1998, à New York et à New Jersey, Les états-unis d'Amérique. Nous rapportons ici la présence d' A . j . japonicus dans nos collections de moustiques dans la capitale provinciale la plus à l'est au Canada, St Jean, Terre-Neuve, en 2013. Cette observation fournit une preuve supplémentaire de la capacité de ce moustique d'élargir considérablement son aire de répartition, impactant potentiellement la connectivité entre les sous-populations à l'échelle mondiale.